Sources of Anxiety and Satisfaction Level of the Mothers Whose Children Hospitalized ‎for Acute Reasons - Gamze Yılmaz; Dilek Küçük Alemdar (Journal of Client-centered Nursing Care, 2019)
Background: To improve the quality of care in pediatric hospitals, health authorities and policymakers should evaluate the satisfaction of the clients. This study was conducted to determine the sources of anxiety and satisfaction of mothers whose children hospitalized for acute reasons. Methods: It was a descriptive cross-sectional study. The study population comprised the mothers of 8-12 years old children who had been hospitalized in the pediatric department of a state hospital in Turkey because of acute reasons. Of them, a total of 341 mothers were recruited by convenience sampling method. The study data were collected by the mother-child information form, parent anxiety resources scale (PARS), evaluation form of problems faced by parents of children with an acute disease (EFPEPCAD) and PdsQL health care parental satisfaction scale. Then, the obtained data were analyzed by descriptive analysis procedures and t test in SPSS. Results: The mean±SD age of the mothers was 32.28±7.24 years. About 61.8% of the children had previous hospital experience, and 77.4% had been hospitalized because of the respiratory tract diseases. The mean±SD score of the mothers from the PARS, EFPFPCAD, and  PdsQL was 142.3±45.10, 34.17±7.65, and 58.60±28.87, respectively. It was also determined that the PARS and EFPFPCAD scores of the working mothers and those whose children were previously hospitalized were significantly higher (P<0.05). Conclusion: It was concluded that mothers had experienced a high level of intense anxiety and moderate satisfaction. To reduce the anxiety of the mothers and to identify the problems they face, the health care team should hold pre-admission programs, inform the parents about their children’s disease, and make them aware of the hospital environment. By taking these measures, the satisfaction levels of the parents may increase.